A Contribution Towards the New Zealand's Tax Reform - B. Laabas; W. A. Razzak (Economics and Econometrics Research Institute (EERI), 2010)
We use the work-leisure choice model to estimate equilibrium labour supply (hours-worked) in New Zealand and Australia over the period 2000 – 2008. We then stochastically solve the model over a future period from 2010 to 2015, and then re-solve it under six different tax policy scenarios for New Zealand. We evaluate the welfare and relative productivity implications of each policy.
Keywords: C63; E62; J22; 330; Taxes; labour supply; welfare and productivity